2022
DOI: 10.18006/2022.10(4).679.688
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox: An Update on Current Knowledge and Research Advances

Abstract: The resurgence of the disease in humans that is very similar to smallpox called monkeypox (MPX) disease, caused by the monkeypox virus (MPXV), is the dominant topic of discussion in the scientific and popular press around the world right now. This is taking place as the world celebrates the historic accomplishments made in the fight against the Coronavirus Disease (COVID-19) pandemic MPX is currently thought to pose a risk to the general public's health, particularly in areas with high rates of MPXV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 61 publications
0
59
0
Order By: Relevance
“…The weight at birth was classified as low if the weight of the child was <2.5 kg and normal if >2.5 kg. The z-scores of three anthropometric indices namely height-for-age, weight-for-age, and weight-for-height were used to assess a child's nutritional status as suggested by WHO ( 9 ). The z-score indicates how far a given result deviates from the mean, and it is commonly used to normalize data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight at birth was classified as low if the weight of the child was <2.5 kg and normal if >2.5 kg. The z-scores of three anthropometric indices namely height-for-age, weight-for-age, and weight-for-height were used to assess a child's nutritional status as suggested by WHO ( 9 ). The z-score indicates how far a given result deviates from the mean, and it is commonly used to normalize data.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, it is nearly impossible to prove whether the main risk factors for developing an ARI from viruses and bacteria originate from the nose, trachea (windpipe), or lungs ( 3 – 5 ). Children, elderly, and people with immune system abnormalities are especially vulnerable ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…To stop the spread of MPXV infections, a successful strategy involving the repurposing of bioactive phytochemicals and existing pharmaceuticals is required. [25][26][27] Saho et al 28 identified that Tipranavir, Cefiderocol, Doxorubicin, and Dolutegravir were the potential drugs among the FDA approved list for monkeypox virus. 28 Similarly, Odhar et al 20 identified that tetracycline (antibiotics) strongly inhibits cysteine proteases of monkeypox virus.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…The precision and accuracy of the models are compared based on error criteria indices while a comprehensive database from different continents issued by global organizations is used to evaluate the proposed models. A globally concerted effort toward the practice of open data sharing and open science priorities is required to generate data and gain adequate knowledge on Monkeypox, which is crucial to rapidly tackle the epidemic and reduce long-term human MPXV infection [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%